Elaboração de um projeto de rações alternativas para pequenas criações de aves e peixes de cinco comunidades rurais de Igarapé-Miri, Pará: uma experiência desenvolvida a partir de um Estágio Institucional obrigatório - MIRANDA, Juciene Lobato (2023)
The report presents the experience of elaborating an alternative feed project developed during a mandatory Institutional Internship of the Technology in Agroecology course, at the Federal University of Pará, Campus Abaetetuba, carried out at the Secretariat for Economic Development and Labor (SEDET) of the City Hall of Igarapé-Miri. The project aims to create more favorable conditions for the production of alternative feed for feeding small chicken and fish farms, using products taken advantage of by the participating communities and families. The experience of the working world provided by the Institutional Internship was essential for the development of the project, in addition to enabling the engagement of the future professional technologist in Agroecology in a context that allowed her to dialogue with rural communities, so that their demands could be contemplated in the drafting of the project.